Legal Protection for Contract Work Service Providers Due to Contractor Default in Road Paving Construction Services Contracts Based on Law Number 2 of 2017 Concerning Construction Services - Rico Altito Deanova Sidebang; Roida Nababan; Besty Habeahan (Indonesian Journal of Business Analytics, 2025)
Contract service providers are often in a weak position in the implementation of construction service contracts, especially when the main contractor commits a breach of contract, such as through work delays or work that does not meet specifications. Therefore, this study aims to examine the forms of legal protection for contract service providers who suffer losses due to contractor default and examine the legal remedies that can be taken by these service providers. The research method used is a normative juridical approach with qualitative analysis techniques of laws and regulations, legal doctrine, and a case study of the Dolok Sanggul Siborong-borong asphalting project. The results show that legal protection for contract service providers can be carried out preventively through detailed contract agreements, performance guarantees, and business certification. As for repressive protection, protection is provided through efforts to summons, lawsuits for breach of contract, contract termination, and reporting to supervisory institutions. In the context of work delays, service providers can also take litigative and non-litigative routes such as mediation, arbitration, and court. Therefore, it is important for contract service providers to fully understand the contents of the contract and legal procedures to protect their rights fairly and proportionally.